A STUDY ON FINANCIAL PERFORMANCE OF ICICI BANK - Nitish Kumar Singh (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2019)
ICICI become the main Indian organization and the principal bank or monetary foundation from non–Japan Asia to be recorded on the NYSE. This examination is insightful in nature. The fundamental motivation behind this investigation is to study the monetary exhibition of ICICI bank utilizing camel investigation. This investigation is logical in nature. Auxiliary Data is gathered from yearly reports, books, diaries and periodicals. The gathered information has been investigated utilizing proportion examination. The examination infers that ICICI bank was in a developing pattern and liquidity boundaries were on the top position. The development of any economy depends on the monetary framework won in it. The significant segments of the monetary framework are monetary resources, monetary middle person/establishment, monetary business sectors, monetary instruments and monetary administrations. A monetary middle person plays a prevailing part in the framework. Monetary middle people incorporate financial framework, protection, improvement banks and other monetary associations. Execution assessment of the banking area is a powerful measure and marker to check the dependability of monetary exercises of an economy. The current examination centers around the individual assessment of ICICI Bank. The investigation embraces an insightful and unmistakable exploration plan. Key words-Ratio analysis, Management Efficiency, Earning Ratio, Asset Quality, Private Banks